Superfoods for dummies - Agin, Brent; Jegtvig, Shereen (John Wiley, 2009)
Research shows a healthy diet incorporating a variety of 'superfoods' can help anyone maintain a healthy weight, fight disease, and live longer. This title provides readers with the information they need to purchase, prepare, and incorporate these superfoods into their everyday diet - and avoid trips to the doctor